Impressão 3D como recurso para o ensino e aprendizagem de citologia - Cruz, Denys Santos da (2022)
The use of digital teaching instruments or materials in schools has always aroused interest and curiosity in most students, however, we know that in some school environments there is a lack of material resources that make it difficult to carry out experimental activities. To solve this problem, teachers improvise materials in order to apply a practical class. In this context of absence of material, 3D printing technology makes a relevant contribution to minimize it, because it is a resource that allows the printing of pedagogical materials, which can help the teaching of different areas, where the contents are still abstractly presented, like cells that are invisible to the naked eye. In addition, 3D printing contributes to the construction of concrete materials in a threedimensional format that were previously only accessible virtually, leaving the classes very abstract for the student, such as cells that are invisible to the naked eye. However, this technology is still not widely used by teachers, perhaps due to the lack of adequate preparation for them. Therefore, this research aimed to contribute to the teaching of Biology, for the subarea of Cytology, with a virtual 3D printing course. The approach of this research was qualitative and quantitative and the method was exploratory research. The research subjects are high school biology teachers and students from the Federal Institute of Education, Science and Technology of Amazonas — Manaus Industrial District Campus (IFAM/CMDI). For data collection, digital questionnaires were used, made available through a link on the Google form, containing open and closed questions, for further analysis and interpretation of the data.Finally, this research, in addition to contributing to the production of a virtual course on how to use the 3D printer to improve learning in Cytology classes, also contains: a digital repository of cell files for printing and a project based on the active methodology of learning in a project involving 3D Printing and Cytology, to be applied with students. The course is available on the digital learning platform Moodle, belonging to IFAM.